2006
DOI: 10.1007/s00384-006-0241-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of microsatellite instability in colorectal carcinoma at an Indian center

Abstract: Our study indicates a similar rate of incidence of MSI in colorectal cancers in the Indian cohort compared to the West (10-15%) despite lower incidence of colorectal cancers and predominance of rectosigmoid tumors in the Indian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…25 A recent study from north India by Dubey et al reported MSI-high in 22% patients. 26 Earlier, two studies from India by Pandey et al 27 and Malhotra et al 28 have reported MMR protein loss from 17.8-19.9%. But both had reported their study with only 2 antibodies, i.e.…”
Section: Discussionmentioning
confidence: 96%
“…25 A recent study from north India by Dubey et al reported MSI-high in 22% patients. 26 Earlier, two studies from India by Pandey et al 27 and Malhotra et al 28 have reported MMR protein loss from 17.8-19.9%. But both had reported their study with only 2 antibodies, i.e.…”
Section: Discussionmentioning
confidence: 96%
“…Total RNA isolation, RT-PCR and quantitative PCR were performed as previously described (52)(53)(54). Primer sequences used were as previously described (39,52).…”
Section: Reverse Transcription Polymerase Chain Reaction (Rt-pcr) and Pcr Primersmentioning
confidence: 99%
“…Western blot analysis: Western blot analysis was performed as previously described [ 22 , 35 ], using a primary monoclonal antibody against CCND1 and β-ACTIN obtained from Cell Signalling, Danvers, Massachusetts, USA. Quantification of blot was performed by use of ImageJ software from NIH, USA ( ) as described previously [ 27 , 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…The predicted sizes of detected protein bands in kDa are shown on the left side. The average of three independent densitometry analyses of CCND1 and β-ACTIN is shown above (right side) by use of Image J software from NIH, USA ( ) as described previously [ 27 , 29 , 30 ].…”
Section: Figures Scheme and Tablesmentioning
confidence: 99%